Balinese Parents’ Involvement on Promoting Digital Citizenship Values: From Ethnopedagogy Perspective - Widhiasih, Luh Ketut Sri (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2024)
The rapid changes of digital technology should be followed by assistance from the adult to the young users. Parents should take a chance to involve in their children digital life and promoting the values of digital citizenships, so that the children can be a good digital citizen who responsible and use digital technology in appropriate way. This study is conducted by on descriptive qualitative design to identify and describe parents’ involvement on promoting digital citizenship values seen from ethnopedagogy perspectives, specifically on Balinese setting. The participants of this study were 40 students who learned about digital citizenship values and children from Balinese parents. The information gathered by using close questionnaire, open questionnaire, and interview to the participants. The instruments used were list of close questionnaire questions, list of open questionnaire questions, and list of interview questions. After the data were gathered, the data analysed using Interactive Model. The results indicated that parental involvement was needed by the children and parents had already done that. The unique thing was that the parents did not have clear concept of digital citizenship but able to promote the values of digital citizenship to their children. They used their local language as the mother tongue, Balinese language in delivering their messages and advices about the values. The parents also strengthen the families and local culture and norms related to digital citizenship, such aa politeness in communication (anggah ungguhing Basa Bali), respect, keeping social relationship (menyama braya), and balancing right and responsibility.